RETRACTION Saputra, M., Arsil, A., Ardo, O., Ahmed, M., Mortezo, A. L., & Tulyakul, S.. (2024). Diferencias en el efecto de los deportes aeróbicos y la motivación para hacer ejercicio en la aptitud física de los estudiantes (Differences in the Effect of aerobic sports and exercise motivation on students’ physical fitness). Retos, 53, 374–380. https://doi.org/10.47197/retos.v53.102478 - RETOS, RETOS (Retos, 2025)
Saputra, M., Arsil, A., Ardo, O., Ahmed, M., Mortezo, A. L., & Tulyakul, S.. (2024). Diferencias en el efecto de los deportes aeróbicos y la motivación para hacer ejercicio en la aptitud física de los estudiantes (Differences in the Effect of aerobic sports and exercise motivation on students’ physical fitness). Retos, 53, 374–380. https://doi.org/10.47197/retos.v53.102478Retraction of the article by the editor of the journal. There has been several clear and conclusive proofs that there has been a manipulation of the authorship of the article. The accepted Word document was sent with the names of the authors that appeared in the “Corrections for the edition” message so that they could only make the orthographical corrections that were necessary. The corresponding author (or whoever hurt him) changed the authors of the aforementioned Word document that was sent to them, returning a document together with these corrections made with new authors, all without any express notification, without any document explaining the changes made accepted by all the authors and, of course, without express authorization from the journal Retos between both moments. With this fraudulent document the galleys were made and the article was definitively published, assigning it the corresponding DOI.Autores en el Word del artículo enviado a revisión: 3Autores en el PDF publicado con los autores modificados: 6Diferencia de los autores entre ambos momentos: +3 (Mottakin Ahmed, Alonzo L Mortejo, Singha Tulyakul)